Implementation of Street Vendor Management and Empowerment Policies (Cik Puan Pekanbaru Market Study) - Radhatul, Atika; Yuliani, Febri (CV. Rayyan Dwi Bharata, 2024)
Street vendors are one of the businesses in the informal sector. The increased number of street vendors, especially in Pekanbaru City, impacts various sectors, including traffic continuity, sublimity, and the immaculacy of the city. The rapid growth of street vendors requires comprehensive efforts from policymakers. Not all traditional markets are managed by the government as street vendors. Only two of the many markets, one of which is Cik Puan Market. The regulations used in this research are Pekanbaru Mayor Regulation Number 100 of 2015 Concerning the Structuring and Empowerment of Street Vendors. This research aims to find out and analyze the mechanism for implementing policies for structuring and empowering street vendors at Cik Puan Market. This research used qualitative research methods with a descriptive approach so the problems can be solved significantly. The results of the research show that (1) communication went quite well. Budget resources and SOP for structuring and empowerment street vendors at Cik Puan Market are not yet available. (2) Mechanism for implementing regulations regarding structuring and empowerment has not been implemented optimally. This is because there are still points in the regulations that have not been implemented in structuring and empowerment at Cik Puan Market. There is no facilitation of access to financing and facilitation of trading facilities for street vendors at Cik Puan Market.